Analiza powiazan pomiedzy rynkami kapitalowymi wybranych krajow grupy wyszehradzkiej - Adam P. Balcerzak; Marcin Faldzinski; Michal Bernard Pietrzak; Tomas Meluzin; Marek Zineker (Institute of Economic Research (IER), 2015)
– Increasing globalization contributes to the growth of the interdependencies between capital markets. This phenomenon is becoming a significant exogenous factors influencing the effectiveness of national economic policies and it impacts on the risk management processes at the microeconomic level. Therefore, the identification of the linkages between capital markets and the analysis of changes in the strength of these relationships over time, can be the source of an important guidelines for national macroeconomic policy makers and can become an essential part of managing the risks associated with the influence of capital markets. Thus, the main objective of the proposed article is to analyze the interdependence between capital markets of selected countries of the Visegrad Group: Poland, Czech Republic and Hungary. The analysis of the relationship between these markets was supplemented with verification of their linkages with German capital market, which is quite close geographically, and additionally is usually considered as one of the leading markets in the European Union. In the econometric research DCC-GARCH model with the t-student conditional distribution was applied. The econometric analysis was done for the period 1997-2015, which gives the possibility to verify the trends in the evolution of interdependencies between the selected markets, measured here by conditional correlations.
Keywords: D53; C32; 330; interdependences among capital markets; conditional variance and correlations; capital market; DCC-GARCH model; Visegrad Group